2017
DOI: 10.5089/9781475592153.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Crises

Abstract: A key objective of fiscal policy is to maintain the sustainability of public finances and avoid crises. Remarkably, there is very limited analysis on fiscal crises. This paper presents a new database of fiscal crises covering different country groups, including low-income developing countries (LIDCs) that have been mostly ignored in the past. Countries faced on average two crises since 1970, with the highest frequency in LIDCs and lowest in advanced economies. The data sheds some light on policies and economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Avoiding fiscal crises is also important because it has implications for economic growth and the development agenda. Fatas and Mihov (2013) showed that volatile fiscal policy lowers economic growth, and work by Gerling et al (2017) suggests fiscal crises can have long-term implications for GDP per capita. As such, it is important to understand what may be causing the crises and how to avoid them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding fiscal crises is also important because it has implications for economic growth and the development agenda. Fatas and Mihov (2013) showed that volatile fiscal policy lowers economic growth, and work by Gerling et al (2017) suggests fiscal crises can have long-term implications for GDP per capita. As such, it is important to understand what may be causing the crises and how to avoid them.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on fiscal crises and on early warning indicators is limited, although it has expanded in recent years. Most of the past literature focused on sovereign external debt defaults alone, although more recent papers (Gerling et al, 2017) have looked at more comprehensive definitions of fiscal crises, including access to official financing and implicit domestic default (high inflation). There is also a growing interest in leading indicators of fiscal crises (or fiscal distress), partly motivated by the global financial crises.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the behavior of capital flows around fiscal crises, the analysis uses the database of fiscal crises prepared by Gerling et al (2017). Those authors define fiscal crises as periods of extreme funding difficulties that result in a disruption in the normal debt dynamics and in the 13 Public and publicly guaranteed multilateral loans include loans and credits from the World Bank, RDBs, and other multilateral and intergovernmental agencies.…”
Section: Datamentioning
confidence: 99%
“…The threshold for emerging markets and low-income developing countries is 100 percent. Finally, a loss of market confidence crisis occurs in years of extreme market pressures, when either the country loses market access 22 or the price of market access surpasses a threshold of 1,000 basis points for the spreads, which is widely seen as market participants' psychological barrier (Gerling et al, 2017).…”
Section: Appendix 1 Definition Of Fiscal Crisesmentioning
confidence: 99%
See 1 more Smart Citation